130k views
3 votes
Solve for M.

(m/9)+(2/3)=(7/3)

2 Answers

5 votes

Answer:

15

Explanation:

khan

User Tianran Shen
by
5.5k points
3 votes

Answer:

m= 15

Explanation:

first you subtract 2/3 from both sides (m/9)+(2/3)-(2/3)= (7/3)- (2/3)

now you will have (m/9)= (5/3)

to get (m) on its own you have to multiply the both sides by 9

(m/9) times 9= (5/3) times 9

m= 45/3 or 15

Answer check:

substitute (m) for 15

(15/9)+(2/3)= (7/3)

first you should simply (15/9), so all of them will have a common denominator

(5/3)+(2/3)=(7/3)

(7/3)=(7/3)

User Connie King
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.